A COMPARATIVE STUDY OF THE FIQH APPROACH TO THE HADITH ON MENSTRUATION - Fauzizah, Anik; Masruri, Muhammad (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2023)
Menstruation is a woman’s nature that cannot be avoided and is closely related to her daily worship activities. Menstruation is a very complicated discussion because the blood that comes out of each woman is different. Therefore, it is an obligation for a woman to learn about the law of menstruation, because learning things that are a condition for the validity and invalidity of an act of worship is fardhu ‘ain. Therefore, the author is interested in researching how a comparative study of the fiqh approach in the hadith about menstruation with the aim of providing understanding and also becoming one of the references for women in understanding the problem of menstruation which is reinforced by shar’i arguments and the opinions of the scholars of the four madhhabs who have been recognised for their scientific capabilities. This study uses the library research method to analyse it and collect some literature then understand and analyse systematically and can synthesise the literature. The findings obtained are that the scholars of the fiqh madhhabs differ in several respects, including differences in defining menstruation, the age of women who experience menstruation, and the details of the prohibition of women who are menstruating. The difference is also based on a different understanding of the hadith that is used as a benchmark.[Haid adalah kodrat wanita yang tidak bisa dihindari dan sangat erat kaitannya dengan aktifitas ibadahnya sehari-hari. Haid merupakan pembahasan yang sangat rumit karena darah yang keluar dari setiap wanita itu berbeda. Maka dari itu sudah menjadi kewajiban seorang wanita mempelajari mengenai hukum haid, karena mempelajari hal-hal yang menjadi syarat keabsahan dan batalnya suatu ibadah adalah fardhu ‘ain. Oleh karena itu penulis tertarik untuk meneliti mengenai bagaimana studi komparatif terhadap pendekatan fiqh dalam hadis tentang haid dengan tujuan bisa memberikan pemahaman dan juga menjadi salah satu rujukan bagi wanita dalam memahami masalah haid yang diperkuat dengan dalil-dalil syar’i dan pendapat para ulama’ empat madzhab yang telah diakui kapabilitas keilmuannya. Penelitian ini menggunakan metode library research untuk menganalisanya dan mengumpulkan beberapa literatur kemudian memahami dan menganalisa secara sistematis serta dapat mensitesis literatur. Temuan yang didapatkan adalah bahwa ulama’ madzhab fiqh berbeda pendapat dalam beberapa hal di antaranya yaitu perbedaan dalam mendefinsikan haid, usia wanita yang mengalami haid, serta perincian larangan wanita yang sedang haid. Perbedaan itu juga di dasarkan pemahaman yang berbeda mengenai hadis yang dijadikan sebagai patokan].